Pengaruh Kemampuan Menghadapi Konflik dan Kritik Terhadap Hubungan Sosial - Agustinus Ndraha; Famahato Lase; Elizama Zebua; Mondang Munthe (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Social relationship abilities can be improved by the ability to deal with conflict and criticism. The aim of the research is to reveal the influence of the ability to deal with conflict (X1) with the ability to deal with criticism (X2), using a quantitative associative strategy method. The research location was SMP Negeri 2 Gido, the research population was all class VIII students and the sample was taken purposively as many as 60 people. The data collection instrument was a closed questionnaire which was distributed to a number of respondents. Data were analyzed using multiple linear regression analysis to answer research questions according to the proposed hypothesis. The research results concluded that the ability to deal with conflict (X1) partially had a significant effect on improving social relations (Y). The regression coefficient value for the variable ability to deal with conflict is negative, namely 0.071 and every 1.00% increase in ability will be followed by an increase in social relations of 0.071%. The ability to face criticism (X2) partially has a significant effect on increasing social relationship abilities (Y). The regression coefficient value for the ability to face criticism is positive, namely 1.102 and for every 1.00% increase in the ability to face criticism, it will be followed by an increase in social ability of 1.102%. Variables X1 and X2 together have a significant effect on variable Y and every increase in X1 and the contribution of the influence of variables X1 and it is recommended for school counselors to provide special guidance and counseling services to handle, develop and improve students' social abilities.